2007
DOI: 10.1086/519560
|View full text |Cite
|
Sign up to set email alerts
|

A Supermassive Black Hole Fundamental Plane for Ellipticals

Abstract: We obtain the coefficients of a new fundamental plane for supermassive black holes at the centers of elliptical galaxies, involving measured central black hole mass and photometric parameters that define the light distribution. The galaxies are tightly distributed around this mass fundamental plane, with improvement in the rms residual over those obtained from the M BH -j and relations. This implies a strong multidimensional link between M -L BH central massive black hole formation and global photometric prope… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 24 publications
2
31
0
Order By: Relevance
“…Hopkins et al (2007a) find that there exist correlations in the residuals of fits such as the M BH -and Magorrian et al (1998) relations; for example, at fixed the residual SMBH mass scales approximately as $M 0:72 b , and at fixed M b the residuals scale as $ 1.40 . By marginalizing over two parameters-M b and either or R e -they found a best-fit BHFP (analogous to that observed for elliptical galaxies; Dressler et al 1987;Djorgovski & Davis 1987) which minimized these residual correlations with the form M BH $ M 0:72 b 1:4 , both in simulations (Hopkins et al 2007a) and for observed systems (Barway & Kembhavi 2007;Hopkins et al Fig. 7.-SMBH growth histories for three different disk models-Sb (solid line), Sc (dashed line), and Sd (dashYdouble-dotted line)-and three different SMBH seed masses-M BH; i ¼ 10 4 (blue), 10 5 (black), and 10 6 (red ) h À1 M .…”
Section: Remnant Propertiesmentioning
confidence: 70%
See 1 more Smart Citation
“…Hopkins et al (2007a) find that there exist correlations in the residuals of fits such as the M BH -and Magorrian et al (1998) relations; for example, at fixed the residual SMBH mass scales approximately as $M 0:72 b , and at fixed M b the residuals scale as $ 1.40 . By marginalizing over two parameters-M b and either or R e -they found a best-fit BHFP (analogous to that observed for elliptical galaxies; Dressler et al 1987;Djorgovski & Davis 1987) which minimized these residual correlations with the form M BH $ M 0:72 b 1:4 , both in simulations (Hopkins et al 2007a) and for observed systems (Barway & Kembhavi 2007;Hopkins et al Fig. 7.-SMBH growth histories for three different disk models-Sb (solid line), Sc (dashed line), and Sd (dashYdouble-dotted line)-and three different SMBH seed masses-M BH; i ¼ 10 4 (blue), 10 5 (black), and 10 6 (red ) h À1 M .…”
Section: Remnant Propertiesmentioning
confidence: 70%
“…As the sample of robust SMBH measurements has increased (Kormendy & Richstone 1995;Kormendy 2004) several black hole-host galaxy correlations (see Novak et al 2006 for a review) have been proposed, including central velocity dispersion (Ferrarese & Merritt 2000;Gebhardt et al 2000a;Tremaine et al 2002), bulge mass/luminosity (Kormendy & Richstone 1995;Magorrian et al 1998;McLure & Dunlop 2002;Marconi & Hunt 2003;Häring & Rix 2004), light concentration (Graham et al 2001;Graham & Driver 2007), and binding energy (Aller & Richstone 2007). Recently, it has been suggested that these observed correlations may be projections of a ''black hole fundamental plane'' (BHFP: Hopkins et al 2007aHopkins et al , 2007bAller & Richstone 2007;Barway & Kembhavi 2007), analogous to that describing the structural properties of elliptical galaxies (Dressler et al 1987;Djorgovski & Davis 1987), that is manifest as a tilted bulge binding energy correlation. These relationships are indicative of an intimate connection between SMBH growth and galaxy formation/ evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested that departures from the M • −σ e relation correlate with a third, structural, parameter, such as R eff or the stellar mass of the bulge M bul (Marconi & Hunt 2003;de Francesco, Capetti & Marconi 2006;Aller & Richstone 2007;Barway & Kembhavi 2007;Hopkins et al 2007a). This has come to be known as the black hole Fundamental Plane (BHFP), and both its existence and origin have been a subject of uncertainty.…”
Section: The Black Hole Fundamental Planementioning
confidence: 99%
“…This article investigates the fundamental planes for SMBHs 1 involving the parameters M bh , R e , and h i e (Barway & Kembhavi 2007), M bh , R e , and ( Marconi & Hunt 2003;de Francesco et al 2006;Aller & Richstone 2007;Hopkins et al 2007), and for the first time M bh , , and n. In x 2, it is explained why a previous claim for a small ''total'' scatter (0.19 dex) about the M bh -R eh i e plane was the result of a miscalculation. In x 3, it is revealed that the galaxies that deviate from the M bh -relation, giving rise to the M bh --R e , M bh --L, and M bh --n relations with less scatter than the M bh -relation, are predominantly barred galaxies.…”
Section: Introductionmentioning
confidence: 99%